YOUTH EVENT MANAGEMENT POTENTIAL AND SOCIAL DEVELOPMENT IN CHANGING WORLD - Semchuk, Zhanna; Koshovyi, Bohdan-Petro; Kramar, Ruslana (Global Prosperity, 2021)
In this article, we have considered the complex problem of developing and realizing the potential of young people in the light of the challenges that arise in the modern world. Young people are a vulnerable social group for whom state and local support is essential. Problems in employment can shake the incentive for young people to develop their potential. We investigated the impact of educational and social space on the development of one of the components of youth potential - potential in event management. We emphasized that the development of this component can be a good impetus for intensifying the entrepreneurial activity of young people. However, youth employment and entrepreneurship in event management need care from the state and intensification of informal social control mechanisms. We have formed recommendations that will allow integrating the processes of social development and development of youth potential in event management. This work can be helpful for public authorities, educational institutions and public organizations. To prevent conflicts of interest, the Chairman of the Editorial Board managed the entire editorial process for this article according to the ethical standards of Global Prosperity (http://gprosperity.org/index.php/journal/pol)